Molecular Breeding for Developing A New Upland Rice Variety ‘Bio Patenggang Agritan’ - Dwinita Wikan Utami; Maulidia Rahmawati; Siti Yuriyah; Ahmad Dadang; Siti Nurani; Nurul Jadid (Jurnal AgroBiogen, 2019)
Situ Patenggang is an elite upland rice variety well-accepted by farmers, but recently this variety started to be attacked by blast disease (Pyricularia grisea) that causes yield loss up to 50%. To overcome this problem, Bio Patenggang variety has been developed through molecular breeding using blast-resistant monogenic lines as donor parents. The aim of this research was to present molecular breeding approach of Bio Patenggang development, including steps from the phenotypic selection on candidate lines to the genotypic analysis assisted by molecular markers. The phenotypic performances were assessed using Distinctness, Uniformity, and Stability (DUS) testing by following the standard method stated in the rice test guidelines. The genotypic analyses were performed using foreground and background markers. Four BC3F7 lines were selected as the candidates of the Situ Patenggang-derived variety. Based on ANOVA and Principal Component Analysis (PCA), phenotypic performances of the four lines demonstrated no significant differences with that of Situ Patenggang. The selected lines have also passed the foreground analysis confirming that the lines contained Pita, Pii, Pik-p, and Pia last resistance genes. Background analysis showed that the selected lines demonstrated agronomic perfomances very similar to that of Situ Patenggang. Association analyses showed that 14 markers were associated with the target traits and 10 out of the 14 markers were identified as co-segregation markers. The four selected lines, therefore, were proposed to be released as Situ Patenggang-derived variety. One of the lines (Sta-8-S15-TB16) has been approved to be released as a new variety, namely ‘Bio Patenggang Agritan’.